Assessment of Foot Ulcer and Peripheral Neuropathy in Diabetic Patients (KYAMC Journal, 2023)
Background: One of the most common complications of diabetes mellitus in lower extremity is the diabetic foot ulcer. There are numerous risk factors, among those peripheral neuropathy is the most important risk factor for diabetic foot ulceration. Objectives: To assess the diabetic foot ulcer, probable risk factors and the relationship of diabetic foot ulcer with peripheral Neuropathy. Materials and methods: This cross sectional study was done in the department of General Surgery, Rangpur Medical College Hospital, Rangpur, Bangladesh between May, 2015 to November 2015. 50 patients with diabetic foot ulcer were selected by purposive sampling method. Results: In this study, 60% of patients were above 60 years of age. 82% of patients were male and 18% were female. All patients were with uncontrolled diabetes mellitus and 80% of patients had blood glucose level between 11-20 mmol/L. HbA1c level found >7 in 68% of patients. 72% patients had history of trauma. 66% of the patients were smoker. None of the patients was alcoholic. Peripheral arterial disease was present in 24% patients. 72% patients had peripheral neuropathy. Conclusion: This study may help to raise the awareness among patients and professionals, ultimately which will help to take initiatives for early diagnosis and treatment of high risk patients.KYAMC Journal Vol. 13, No. 04, January 2023: 214-217